(untitled) (Research, Society and Development, 2020)
The mind and body within the historical processes were placed in epistemological paradigms that diverged and were not accepted as instances that communicated and influenced the body. However, they are instances that communicate and influence the subject’s well-being, and their lack of conception of transversality and multifactoriality cause a fragmentation of understanding about the subject in the dynamic processes of subjectivity and disease and health.This study is of a qualitative nature that aimed to discuss how the literature has been describing about the way emotional conditions corroborate psychosomatic diseases through psychoanalytic theories. As a method, a bibliographic review was carried out, using articles published in 2014 and 2018, in the following databases LILACS, MEDLINE, IBECS and INDEX PSICOLOGIA. Reflections on the interactions between the mind, body and emotional influences on the process of becoming ill or worsening on the illness were discussed, as well as advances on the psychosomatic phenomenon. In conclusion to this, it was possible to verify the expansion regarding the biopsychosocial understanding of human being.